Characterization of Magnetic and Density Properties on Barium Ferrite with MnO2 Addition - Astari, Ratih Resti; Kuncoro, Handoko Setyo; Rahman, Didit Nur; Kristiantoro, Toni (Balai Besar Keramik, 2017)
The addition of MnO2 in synthesis of barium ferrite magnet were prepared by powder metallurgy method with variation formula of MnO2 0%, 0.1%, 0.2%, 0.3%, 0.5% and 1% sintered at 1175 ÂºC. Material characterization includes X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and permagraph were employed to investigate the effect of MnO2 addition to magnetic properties and sample density. Hysteresis curve using permagraph showed that the addition of MnO2 have an effect on the increasing of magnetic properties and density. Remanence induction (Br), coercivity (Hc) and density (Ï) reached the maximum value of 1.36 kG, 2.757 kOe and 4.29 g/cm3Â respectivelyÂ on different formula MnO2. The best value of MnO2 addition could be concluded on the addition MnO2 of 0.3% with Br = 1.36 kG, Hc = 2.683 kOe, and Ï = 4.29 g/cm3. The XRD results showed the formed of barium ferrite phase in the sintered sample at 1175ÂºC. While the SEM result revealed that the addition of MnO2 affected the density of barium ferrite particles.